Fostering Creativity in Intercultural and Interdisciplinary Teams: The VICTORY Model - Tang, Min (Frontiers in Psychology, 2019)
Teams are pervasive in the history of mankind. Particularly in our fast-growing modern society, teams composed of members from different cultures and disciplines are quite often used at the workplace. Though widely used, the effectiveness of teams is inconsistent. Meta-analyses report a double-edged effect of diversity on creativity and innovation, suggesting that diversity needs to be tactfully managed if we want to leverage the creative potential of teams. The current paper strives to meet this challenge and makes recommendations on how to foster creativity in intercultural and interdisciplinary teams. It discusses the concepts of teams vs. groups and creativity vs. innovation. Drawing upon sociocultural theories of creativity and innovation, particularly literature reviews and meta-analyses, this paper attempts to identify non-cognitive, cognitive and environmental enablers of team creativity. The VICTORY model offers a summary of these enablers, as it focuses on team (T) and synthesizes both non-cognitive (Vision, Openness, Risk-taking, Yes-I-Can Mindset) and cognitive (Ideation, Combination) antecedents of team creativity. Yet it is only through the combination and integration of environmental factors (including communication, collaboration, and support, among others) that the effect of these antecedents can be fully realized.